Deduction of the conformation of short chain luminescent conjugated polymers from single molecule photophysics - White, J (2001)
The fluorescent transient of single polymers of a PPV derivative, poly(2,5-dioctyloxy p-phenylene vinylene) (DOO-PPV) spin-cast in polystyrene matrix is observed. Having the polymer with low-defect density and length close to its persistent length, the effect of defects on conformation can be investigated. Independent chromophores align in the majority of cases suggesting that the polymer maintains a rod-like structure in the absence of defects. Non-aligned chromophores are the result of defects that introduce 'kinks' in the polymer conformation. (C) 2001 Published by Elsevier Science B.V.